Mapping sectors for high employment and low carbon growth in South Africa - Wills, Nicola Grace (School of Economics, 2023)
South Africa is facing an unemployment crisis, with an unemployment rate of 43.2% by the expanded definition in quarter 1 of 2021. At the same time, the threats of climate change are becoming ever more evident and the world is under increasing pressure to lower its carbon emissions. The distributional effects of a lower carbon growth pathway will be an important part of the overall transition to a lower carbon economy, in South Africa and elsewhere. Previously, sectors have been characterised according to either their employment or carbon intensity, but have not been mapped based on both measures. This dissertation fills this gap by mapping sectors for a prospective high employment and low carbon growth pathway in South Africa. This is done by constructing a two-bytwo typology to explicitly map sectors / subsectors by both their employment multiplier rank and carbon intensity. This mapping lays the basis for providing an understanding of the implications of three policy measures across different sectors. The three policy measures discussed – a wage subsidy, carbon tax and phase out of fossil fuel subsidies – have the potential to jointly help shift the growth pathway of South Africa to higher employment and lower emissions. On the one hand, a wage subsidy applied to all sectors would provide larger benefits for more employment intensive sectors and so incentivise growth therein. On the other hand, the phasing out of fossil fuel subsidies and a more punitive carbon tax would place more financial pressure on relatively capital and carbon intensive sectors. Overall, the focus of this dissertation is to support a ‘Just Transition' to a new growth pathway characterised by high employment and low carbon.